Sourdough "ciabatta" bread enriched with powdered insects: Physicochemical, microbiological, and simulated intestinal digesta functional properties. (August 2021) - Gaglio, Raimondo; Barbera, Marcella; Tesoriere, Luisa; Osimani, Andrea; Busetta, Gabriele; Matraxia, Michele; Attanzio, Alessandro; Restivo, Ignazio; Aquilanti, Lucia; Settanni, Luca
Abstract: Powdered mealworm (MW) and buffalo worm (BW) larvae were used to functionalize sourdough Italian-style breads. Sourdough inoculum was started with Levilactobacillus brevis, Weissella cibaria and Leuconostoc citreum . The doughs were SBS (semolina plus powdered BW larvae and sourdough) and SMS (semolina plus powdered MW larvae and sourdough) whose pHs (4.32 and 4.21, respectively) were higher than that of control (3.81). The highest fermentation quotient (lactate/acetate molar ratio) was recorded in SMS (4.46). LAB reached viable counts of about 10 9 CFU g −1 in almost all doughs. Insects impacted bread VOCs with dodecanal, 2.4-dodecadienal and 2-octenal-2-butyl. SBS and SMS increased the antioxidant capacity of breads by 42 and 69%, respectively. SMS decreased the glucose release in the bio-accessible fraction by 70% reducing the glycemic index of bread. Control breads were more appreciated by the sensory panel than insect-containing breads, though SMS breads were characterized by a slightly lower overall assessment. Highlights: The pH of 14.4% ( w /w) buffalo worm and mealworm doughs were 4.21 and 4.32 Lactic acid bacteria inocula growth was not affected by insect powders Both insect powders generated dodecanal, 2.4-dodecadienal and 2-octenal-2-butyl Bread antioxidant capacity increased with buffalo worm (42%) and mealworm (69%) Mealworm powder decreased glucose release in bread bio-accessible fraction by 70%